Effect of Coconut Shell Liquid Smoke and Water Hyacinth Root Extract on the Growth of Soybean in Mycorrhiza-enriched Saline Soil - Fitria, Roesita Nur; Rahayu, Yuni Sri (LenteraBio : Berkala Ilmiah Biologi, 2024)
Saline soil negatively impacts plant growth, requiring improvements to enhance soybean productivity. This study examined the effects of coconut shell liquid smoke, water hyacinth root extract, and their interaction on soybean growth in saline soil enriched with mycorrhiza. This experimental research using a Randomized Group Design (RGD) with three repetitions, two factors were tested: liquid smoke (0%, 1%, 2%) and water hyacinth root extract (0 ppm, 500 ppm, 1000 ppm). Vegetative parameters included plant height, number of leaves, root length, wet biomass, root nodules, active root nodules, mycorrhizal infection percentage, and phosphorus content. Generative parameters included flowering age, number of pods, and pod biomass. Data were analyzed with Two-Way ANOVA, Duncan test, and descriptive methods. Liquid smoke improved the number of leaves (14.56 strands), root length (37.78 cm), wet biomass (14.44 g), and pod biomass (8.00 g). Water hyacinth root extract enhanced plant height (122.33 cm), number of leaves (14.56 strands), root length (39.44 cm), wet biomass (16.00 g), number of pods (11.78 pods), and pod biomass (9.00 g). The interaction of 2% liquid smoke and 1000 ppm root extract yielded the highest wet biomass (17.67 g) and pod biomass (10.67 g), showing significant synergistic effects for improving soybean growth.